The Leader, His Driver, and the Driver's Wife - Broomfield, Nick (Lafayette Film, 1990)
A poignant image of Apartheid in South Africa through the portrait of Eugène Terre'Blanche, founder of the far-right organization AWB. Throughout the film, Broomfield attempts to set up an interview with the control-obsessed Terre'Blanche, who stubbornly undoes all of the plans in order to prove his power. For the majority of the film, during which Broomfield is unable to obtain an interview with the Leader himself, his attention is drawn to the driver and his wife (JP and Anita Meyer) who are happy to share their views on racial inequality and anticipated revolution. Acutely aware of the all-too-seductive nature of Fascism and the media's historical complicity in that seduction, Broomfield has produced an anti-Triumph of the Will, deliberately lampooning a movement whose power rests as much in grave self-importance as it does in violent intimidation.